On The Character Of Forced Vibrations Of Plates Having A Plane Of Elastic Symmetry - Aghalovyan, L. A.; Aghalovyan. M. L.; Zakaryan, T. V.; Tovmasyan, A. B. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
The spatial problem on forced vibrations of composite plates, having a plane of elastic symmetry, is solved. It is considered that on the facial surface of the plate normal and tangential loads act, which change harmonically over time, and the lower facial surface of the plate is rigidly fixed. For solving such type of problems, the hypotheses of classical and refined theories of plates and shells are not applicable. A fundamentally new asymptotics for the components of the stress tensor and the displacement vector was established, which made it possible to find an asymptotic solution to the problem, which becomes mathematically exact if the external loads are algebraic polynomials from tangential coordinates. The conditions for the occurrence of resonance are derived. It is shown that in such a plate the vibrations are purely flat and anti-flat (transverse). The amplitudes of these oscillations have been determined. The amplitudes of these oscillations are determined. The conditions for the occurrence of resonance are derived, and the values of resonance frequencies are determined. Առաձգական սիմետրիայի հարթություն ունեցող սալերի համար լուծված է ստիպողական տատանումների տարածական խնդիր։ Համարվում է, որ սալի դիմային մակերևույթի վրա ազդում են նորմալ և տանգենցիալ, ժամանակի ընթացքում հարմոնիկ փոփոխվող ուժեր։ Ստորին դիմային մակերևույթը կոշտ ամրակցված է։ Սալերի դասական և գոյություն ունեցող ճշգրտված տեսությունները տվյալ խնդրի լուծման համար կիրառելի չեն։ Գտնված է լարումների թենզորի և տեղափոխման վեկտորի բաղադրիչների համար դասականից սկզբունքորեն տարբերվող ասիմպտոտիկա, որը թույլ է տվել գտնել խնդրի ասիմպտոտիկ լուծումը։ Այդ լուծումը դառնում է մաթեմատիկորեն ճշգրիտ, երբ արտաքին ազդող ուժերը տանգենցիալ կոորդինատներից հանրահաշվական բազմանդամներ են։ Ցույց է տրված, որ տատանումները հանդիսանում են զուտ հարթ և հակահարթ։ Որոշված են տատանումների ամպլիտուդները, արտածված են ռեզոնանսի առաջացման պայմանները, որոշված են ռեզոնանսային հաճախությունները։ Решена пространственная задача о вынужденных колебаниях композитных пластин, имеющих плоскость упругой симметрии. Считается, что на лицевую поверхность пластины действуют нормальные и тангенциальные нагрузки, которые по времени изменяются гармонически, а нижняя лицевая поверхность пластины жёстко закреплена. Классическая и существующие уточнённые теории пластин для решения задачи неприменимы. Установлена принципиально новая асимптотика для компонент тензора напряжений и вектора перемещения, позволившая найти асимптотическое решение задачи, которое становится математически точным если внешние нагрузки являются алгебраическими многочленами от тангенциальных координат. Выведены условия возникновения резонанса. Показано, что в такой пластине колебания являются сугубо плоскими и антиплоскими (поперечными). Определены амплитуды этих колебаний. Выведены условия возникновения резонанса, определены значения резонансных частот.
Keywords: Mechanics